Supernatural Season 2 Disc 3 - Yavneh, Cyrus; Padalecki, Jared, 1982-; Ackles, Jensen; Kripke, Eric.; Manners, Kim.; Shiban, John.; Sgriccia, Phil.; Gamble, Sera.; Singer, Robert; Tucker, Raelle; Edlund, Ben.; Iacofano, Tim.; et al. (Burbank, CA : Distributed by Warner Home Video, 2007)
Sam and Dean Winchester are hunters on the trail of the demon who murdered their mother, and of any other unholy agent of the supernatural. In the aftermath of the car crash, a shocking sacrifice will cements the bond between the Winchester men forever. The brothers make a bone-chilling road trip across America and journey deeper into the mystery of their own destinies.
Croatoan / written by John Shiban ; directed by Robert Singer -- Hunted / written by Raelle Tucker ; directed by Rachel Talalay -- Playthings / written by Matt Witten ; directed by Charles Beeson.
Widescreen format.
Title from container.
Created by Eric Kripke.
Contains episodes from the second season.
Special features: Unaired scenes on "Hunted."
Jared Padalecki, Jensen Ackles.
Keywords: Supernatural -- Drama; Brothers -- United States -- Drama; Murder -- Investigation -- United States -- Drama; Sacrifice -- United States -- Drama; Fate and fatalism -- Drama; United States; Drama; Television programs; Television series; Thrillers (Motion pictures); Suspense television programs